The role of civil society organisations in co-regulating online hate speech in the EU: A bounded empowerment - Barthélémy Michalon (Internet Policy Review)
Civil society organisations (CSOs) have been gradually expanding their role in monitoring the Code of Conduct jointly developed in 2016 by the European Commission and four large social media platforms to counter online hate speech. While their function was initially limited to collecting data and transmitting it to the EU executive, over the years CSOs have not only expressed critical views on the “monitoring exercise” designed to assess the agreement’s effectiveness but also devised ways to support their claims and elevated their involvement in the functioning of the mechanism. Drawing on data from two surveys carried out in 2019 and 2022, over twenty interviews conducted in the same timeframe, as well as reports published by these organisations, this paper provides insights into the evolution of CSOs’ perceptions on the matter and examines how this category of players became closely embedded in the operational side of the Code of Conduct. The evidence presented suggests that civil society has expanded its role beyond the specific task initially entrusted to it by the Commission. Yet, despite this shift, CSOs’ role remains limited to that of a third-party participant, an expression that reflects both the reality and the limitations of their role within the co-regulatory scheme.